Educational knowledge : changing relationships between the state, civil society, and the educational community - Popkewitz, Thomas S. (SUNY series, frontiers in education., 2000)
"Focusing on comparative examination of educational reforms, this book explores the relation of state practices and educational knowledge to changes in culture and economics among nations." "Educational Knowledge brings neo-Marxist theories, world systems, and post-modern cultural and political theories into a conversation about the changes that are occurring in the educational arena. This book will interest not only specialists in the field of education studying educational reform, but also economists, political scientists, sociologists, and comparative historians who examine the functioning of education within the larger context of modernization."--Jacket